THE IMPACT OF BUDGET PARTICIPATION ON AUTONOMOUS BUDGET MOTIVATION: THE MEDIATING EFFECT OF ORGANIZATIONAL COMMITMENT - Wafiroh, Novi Lailiyul (Fakultas Ekonomi Universitas Gresik, 2020)
The aims of this reasearch is to test the effect of mediation of organizational commitments in the impact of budget participation on the motivation of autonomous budgets to companies from various industrial sectors in East Java. Quantitative method is a method used by researchers in conducting this research. Researchers are using SmartPLS software application version 3.0 with SEM-PLS as data analysis technique. This research uses the SEM-PLS model because, in this research, the variables used are latent variables (variables that cannot be observed). The Functional Manager, who participated in drafting the company's budget was able to increase its commitment to reach the target budget set. The higher level of the manager's participation in the company's strategic planning can increase the motivation of autonomous budget managers. The autonomous motivation of employees is known to be influenced by the organizational commitments in a positive direction, or in other words have a significant positive relationship. This indicates that when the commitment of oragnization in the employee is at a high level, the level of autonomous motivation that the employees have is also at a high level (Chong & Chong (2002) and Baerdemaeker & Bruggeman (2015)). The analysis of the data conducted shows that the variable of positive budget participation is influential but not significant to the motivation of the autonomous budget through organizational commitment